Acquired Left Ventricular Hypertrabeculation/Noncompaction in Sarcoidosis—A Rare but Possible Preventable Cause of Myocardial Infarction. Issue 5 (August 2017) - Javed, Fahad; Khan, Shahzeb A.; Sheikh, Azfar Bilal; Mahmood, Sarah; Zia, Nimra; Nadkarni, Girish; Benjo, Alexandre; Altabaqchali, Sayf; Lavie, Carl J.
Abstract : Left ventricular hypertrabeculation/noncompaction (LVHT/NC) is a rare if not unique disorder of endomyocardial morphogenesis. Left ventricle in this condition consists of trabeculations that are both increased in prominence and excessive in number, was hypothesized to be caused by intrauterine arrest of compaction of the myocardial fibers and meshwork. LVHT/NC has been observed to have high prevalence in children as opposed to adults with genetic linkage. Acquired LVHT/NC has been recently reported to be associated with other autoimmune diseases like mitochondriopathy, myotonic dystrophy type 1, essential thrombocythemia, Duchenne muscular dystrophy, and various neuromuscular disorders. We report here an interesting case displaying LVHT/NC in a patient with coexistent neuro-sarcoidosis at an age of 49 years with concomitant non-ST-Elevation Myocardial Infarction. Following diagnosis of LVHT/NC by means of transthoracic echocardiography, our patient was treated with a course of intravenous steroids with resultant improvement in his symptoms. This case is a unique presentation of the association of neuro-sarcoidosis with LVHT/NC with a presumptive complication in the form of non-ST-Elevation Myocardial Infarction due to synergistic interplay of pathophysiological mechanisms of these 2 individual conditions.